PEMBERDAYAAN UMKM MELALUI PUSAT KOMUNIKASI BISNIS BERBASIS WEB (E-COMMERCE) - Rahadhini, MD. (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2012)
ABSTRACT In market mechanism which more open and competitive, domination of market represent prerequisite to increase UMKM competitiveness. So that can be master in market, hence UMKM require to get information easily and quickly, information goodness concerning market produce and also factors of production market. Claimed the existence of participation and role various side especially local government and college to assist and facility access information to UMKM. Exploiting information technology in running business (e-commerce) to small company and UMKM can give flexibility in production, enabling to access to customer quickly. Internet exploiting through e-commerce, enabling UMKM conduct marketing with a purpose to global market, so that opportunity penetrate market export is very possible done. Keywords: UMKM, e-commerce, global market.